Band edge emission of ZnS nanoparticles prepared by excess of thiourea as a source of sulfur - Wageh, S.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Springer, 2013)
We have synthesized ZnS nanoparticles capped with mercaptoacetic acid with band edge emission at 327 nm (3.79 eV). The synthetic procedure for producing the band edge emission is mainly dependent on the refluxing time and on using a high ratio of sulfur source at the preparation time to diminish the sulfur deficiency trapping centers. The effect of refluxing time showed the presence of shallow levels due to the interstitial sulfur and zinc ions for the short refluxing time samples up to 11 h, whereas, the prolonged refluxed samples showed the diminishing of the shallow levels. The photoluminescence exhibits a band edge emission with a narrow full width at half maximum for the dispersed samples in aqueous solution and the photoluminescence excitation elucidated the transition energies of the shallow traps and the band edge. In addition, the bound excitons and the spin-orbit-split off energy transitions are identified from the photoluminescence excitation. Huang Rhys factor S was determined from the difference between the photoluminescence excitation and photoluminescence spectra. The obtained value of S is agreeing well with published value obtained from the temperature dependence of the band gap of ZnS.
Keywords: ZnS; Nanoparticles; UV-Vis Absorption; Luminescence; Luminescence excitation